Identification of Arbuscular mycorrhizal multiplicity in the saline-sodic soils - Srimathi, Priya L; Kumutha, K; Arthee, R; Pandiyarajan, P (International Journal of Agricultural and Biological Engineering, 2014)
This study focused on the Arbuscular mycorrhizal (AM) fungal diversity in the saline-sodic soils based on native spore density and most probable number (MPN) assay. Identification through spore morphology showed existence of five genera in the various crop rhizospheres. The physico-chemical analysis of the native soils revealed that they were saline-sodic with pH ranging from (8.7±0.5) to (9.5±0.6) and habituated five different genera of AM fungi including Glomus, Scutellospora, Acaulospora, Sclerocystis and Gigaspora. Each location revealed presence of varied species of AM fungus namely Acaulospora and Glomus in rhizosphere of maize; Scutellospora and Glomus in tulsi; four isolates of Glomus in onion; Glomus and Sclerocystis in guava; three isolates of Glomus in rice; Glomus in neem and Gigaspora and Glomus in bamboo. The molecular identification through nested PCR analysis showed amplification of 600 bp size in SSU rDNA gene in samples A and C (predominated by Acaulospora and Glomus mosseae respectively). Keywords: AM fungal identification, saline-sodic soil, crop rhizosphere, spore density, nested PCR technology, glomalean fungus DOI: 10.3965/j.ijabe.20140702.007 Citation: Srimathi Priya L, Kumutha K, Arthee R, Pandiyarajan P. Identification of Arbuscular mycorrhizal multiplicity in the saline-sodic soils. Int J Agric & Biol Eng, 2014; 7(2): 56－67.